Relationship Between Knowledge and Attitude with Implementation of Patient Safety Targets in RSUD Yogyakarta - Nur Syarianingsih Syam; , Siti Kurnia Widi Hastuti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Joint Commission International stipulates the International Patient Safety Goals (IPSG) as one of the points in the hospital's international accreditation assessment. In Indonesia the IPSG target was translated by the hospital accreditation committee (KARS) into 6 patient safety targets (SKP) in the 2012 hospital accreditation guidelines (KARS 2012). Yogyakarta Regional General Hospital (RSUD) is one of the class B public hospitals that have received Akreditasi Paripurna, in this case all working groups including patient safety standards at the hospital have been assessed. However, there are still KTD, KNC, KPC, and KTC in Yogyakarta Hospital. This study aimed to analyze the relationship between attitudes and knowledge with the implementation of patient safety goals by nurses in Yogyakarta Hospital. The study used quantitative research methods with a cross sectional research design. Data retrieval is done by distributing questionnaires related to attitudes and knowledge to 80 nurses with the implementation of patient safety goals, the sampling technique with clustered stratified sampling. Data analysis techniques for quantitative analysis with univariate, bivariate (chi square test). Research results of the relationship between knowledge and implementation of SKP showed that the p-value of α (0.631> 0.05), means that there is no relationship between nurse knowledge and the implementation of patient safety goals (SKP). The results of the study of attitude relations with SKP Implementation can be seen that the p-value α (0.045 <0.05), meaning that there is a relationship between nurse attitudes and the implementation of patient safety goals (SKP).